Initial Experience Using the Radiofrequency Needle Visualization on the Electroanatomical Mapping System for Transseptal Puncture - Silvia Guarguagli; Ilaria Cazzoli; Aleksander Kempny; Michael A. Gatzoulis; Sabine Ernst (Cardiology Research and Practice)
Introduction. Transseptal puncture (TSP) is a routine access route in patients with left-sided ablation substrates and is performed safely on fluoroscopy (+/− echocardiographic guidance). We report on our experience using a radiofrequency (RF) needle in an unselected group of patients to demonstrate safety and usefulness of direct tip visualization on the 3D electroanatomical mapping (EAM) system with specific emphasis on total radiation exposure. Methods and Results. We retrospectively reviewed 42 consecutive left-sided ablation procedures with TSP performed using an RF needle guided by fluoroscopy and/or EAM visualization by a single operator. The procedures included atrial fibrillation (n = 33), atrial tachycardia (n = 8), and ventricular tachycardia (n = 1) ablations. Fourteen of 41 patients had congenital heart disease, including 9 patients with previous septal closure. Twenty-two patients had at least one previous TSP. All TSPs were performed successfully and without complications. The overall median fluoroscopy time amounted to 3.2 min and median exposure of 199.5 µGy∗m2. In a subgroup of patients (n = 27), the RF needle was visualized on the EAM system: median radiation time was 0.88 (interquartile range: 0–3.4) min and median exposure 33.5 [0–324.8] µGy∗m2. Conclusions. TSP using an RF needle is an effective technique, also in congenital patients with artificial patch material and in normal patients with multiple previous TSPs. Moreover, the RF needle tip visualization on EAM allows a low (or even zero) fluoroscopy approach.